Effects of foliar Zn application on rice yield and element contents under different Cd levels - SUO Yan-yan; WU Shi-wen; ZHU Jun-jie; PAN Feng-shan; FENG Ying (浙江大学学报. 农业与生命科学版, 2012)
A pot experiment was conducted to investigate the effects of foliar zinc (Zn) fertilization at the late developmental stage on rice growth and yields under different cadmium (Cd) levels, as well as the influence on metal contents such as Zn, Cd, iron (Fe), copper (Cu), manganese (Mn), magnesium (Mg) and calcium (Ca) in different plant parts. And the correlations of these elements in rice grains were also analyzed. The results showed that with elevated soil Cd, rice growth was inhibited. The fresh mass of rice plants was decreased by 14.0% and 15.9%, respectively, when 2.5 or 5 mg·kg-1 Cd was added to the soil; accordingly, the dry mass was decreased by 5.3% and 7.6%, respectively; the yield also was decreased by 27.9% and 48.4%, respectively; in brown rice, the Cd content was 0.35 and 0.65 mg·kg-1, respectively, which exceeded the food safety standard (0.2 mg·kg-1 Cd). There were not obvious effects of foliar Zn application on rice growth and yield. However, Zinc contents in all plant parts increased with foliar Zn application under all Cd levels. Cadmium content in brown rice increased by 41.9% with foliar Zn application at 2.5 mg·kg-1 Cd level, while, it was decreased by 15.4% at 5 mg·kg-1 Cd level. Further analysis revealed that Cd was significantly correlated with Cu, Mn and Mg, but not correlated with Zn in brown rice.